The strength and weaknesses of the varieties of capitalism approach: The case of Central and Eastern Europe - Krzysztof Jasiecki (International Journal of Management and Economics, 2018)
The purpose of the article is to characterize selected theoretical and methodological advantages, controversies, and limitations of the varieties of capitalism (VoC) approach in application to Central and Eastern European (CEE) countries. It indicates the reasons for the usefulness of such an approach for the study of postcommunist capitalism in the region. The application of the VoC is considered as going beyond the dominant approaches to systemic changes in CEE in the 1990s, such as the strategy of neoliberal economic reforms and the "transitology" prevailing among political scientists and sociologists who referred to democratic patterns of change in Southern Europe. After a decade of reforms, due to different trajectories of development in the countries of the region, such interpretations lose their explanatory power. Other ways of analyzing transformations in CEE have become needed. The need for new theoretical inspirations has also been strengthened by the European Union (EU) accession of the same postcommunist countries. The accession has generated a search for a new language of description and analyses of institutional changes in all the countries of the enlarged Union. In this context, the VoC approach seems to fill the theoretical vacuum left by the end of the "transition" debate in the political research on CEE and provides a major post-transition research agenda and has also built a bridge between discourses which were previously separated in the political economy, neo-institutional approaches, economic sociology, and political sciences. The key advantages of the VoC approach are presented, which made these perspectives influential among researchers of institutional changes in postcommunist countries. The theoretical and analytical framework, classifications, typologies, clusters, indexes, indicators, and so on are tested and widely applied as well. Selected weaknesses and limitations of the VoC approach in the application to CEE are also analyzed. Their manifestation is the confusion associated with the use of various classifications of models of capitalism and the functionalistic character of the VoC focusing on explaining the results, but not the causes of the institution's activities, as well on institutional determinism diminishing the significant role of the social factors of change.
Keywords: 650; the diversity of capitalism; models of capitalism; postcommunist variants of capitalism; Central and Eastern European economies